Clinical teaching practices of nurse educators: An integrative literature review - Gcawu, Sybil N.; van Rooyen, Dalena (Health SA = SA Gesondheid, 2022)
Clinical teaching practice of nurse educators is important in the development of clinical competence of undergraduate nursing students, but it is often not done according to best practice standards. This study aimed to summarise the best clinical teaching practices of nurse educators teaching undergraduate nursing programmes. An integrative literature review was conducted according to Whittemore and Knafl’s adapted stages. A systematic search of electronic databases, including EBSCOhost and ScienceDirect, for applicable papers from January 2001 to June 2021, was followed by a manual search. The review resulted in selection of 67 papers, and critical appraisal had been completed by two independent reviewers using relevant critical appraisal tools. Papers that were selected revealed six main themes, with sub-themes, outlining best practices for clinical teaching, namely: (1) planning for clinical teaching practice: self-preparation and planning for clinical placement; (2) facilitation of students’ clinical learning: orientation of students, planning for clinical teaching and the clinical teaching process; (3) evaluation of students’ clinical skills: reflection by the nursing student and feedback; (4) modelling professional clinical teaching practice: emotional intelligence, self-evaluation, role modelling and continuous professional development; (5) work-based assessment in the clinical environment: clinical assessment process and clinical assessment tools and (6) clinical teaching in the simulation laboratory. The six identified best practices could assist nurse educators to provide comprehensive clinical teaching.ContributionThe review’s results can be used in the development of a best practice guideline for clinical teaching. This guideline will aid nurse educators in achieving best clinical teaching practices.